2014
DOI: 10.1080/13670050.2014.960360
|View full text |Cite
|
Sign up to set email alerts
|

Songs vs. stories: impact of input sources on ESL vocabulary acquisition by preliterate children

Abstract: Research in second language acquisition has paid little attention to preliterate children learning a language which is absent from their environment outside the language class. This study examines the acquisition of English words by 24 French-speaking children aged 35-59 months, who were introduced to 57 words, embedded in stories and songs. Four stories and four songs were randomly spread across four consecutive weekly workshops consisting of play-based pedagogical activities. The impact of the input source, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Stories were most effective in teaching vocabulary. The authors noted that the effectiveness of stories over songs for foreign language learning in this age group echoed earlier findings (Leśniewska & Pichette, 2016). However, song selection is also important: as Pino Juste and Rodríguez López (2010) remarked, many traditional children's songs use quite advanced and archaic language, and might therefore not be a source of meaningful language input.…”
Section: Teacher Strategies and Interaction Practicesmentioning
confidence: 56%
“…Stories were most effective in teaching vocabulary. The authors noted that the effectiveness of stories over songs for foreign language learning in this age group echoed earlier findings (Leśniewska & Pichette, 2016). However, song selection is also important: as Pino Juste and Rodríguez López (2010) remarked, many traditional children's songs use quite advanced and archaic language, and might therefore not be a source of meaningful language input.…”
Section: Teacher Strategies and Interaction Practicesmentioning
confidence: 56%
“…The children's performance, measured by a picture description task, indicated that learning through both songs and choral repetition was more effective than the control condition. Leśniewska and Pichette (2016) found that both songs and stories helped French-speaking English-learning children (35-59 months) recall animate vocabulary items regardless of their L1 vocabulary levels. With the limited empirical research available, it is hard to reach any conclusions about the use of songs and music in L2/FL vocabulary instruction for young learners.…”
Section: Using Multimodal Approachesmentioning
confidence: 92%
“…449–450) himself points out, when songs are directly compared with other procedures used to teach English vocabulary, then much of their advantage disappears. The study by Leśniewska and Pichette (2016) actually found that songs were less effective than stories in developing very young learners' vocabulary. This has very recently been confirmed by Albaladejo Albaladejo, Coyle, and Roca de Larios's (2018) research.…”
Section: Young Learners' Vocabulary Developmentmentioning
confidence: 99%
“…Davis's (2017) review includes three studies of this type focusing on EFL or ESL learners who were five years old or younger. The general conclusions stemming from the review are that songs can contribute to the development of vocabulary knowledge (Coyle & Gómez Gracia, 2014; Davis & Fan, 2016; Leśniewska & Pichette, 2016).…”
Section: Young Learners' Vocabulary Developmentmentioning
confidence: 99%